Analysis of NDNF and SLC1A2 gene expression in the dorsolateral prefrontal cortex of individuals with autism - de Andrade, Ariel Moraes; de Souza, Larysy Raquelly Vidal; Oliveira, Rodrigo Freire; Paiva, Karina Maia; Fiuza, Felipe Porto; de Farias, Pedro Henrique Silva; da Silva Júnior, Roque Ribeiro; Holanda, Maria Vanessa Freitas; de Medeiros Fernandes, Thales Allyrio Araújo; de Góis Morais, Paulo Leonardo Araújo; de Paiva Cavalcanti, José Rodolfo Lopes (Frontiers in Neuroscience, 2026)
IntroductionThis study investigated the expression of NDNF and SLC1A2 in the dorsolateral prefrontal cortex of individuals with Autism Spectrum Disorder (ASD), a region linked to executive functions, emotional regulation, social skills, and sensory processing.MethodsUsing data from the Allen Human Brain Atlas – Autism Study, 17 post-mortem cases (ASD: 9; controls: 8; ages 2–14) were analyzed with in situ hybridization and Nissl staining. Histological images were processed with FIJI-ImageJ and Ilastik software.ResultsNo significant differences in NDNF expression were observed, though a trend toward lower levels in ASD was noted. In contrast, SLC1A2 expression was significantly increased in ASD and showed age-related growth, possibly reflecting neuroinflammatory processes. Nissl staining indicated similar neuronal density between groups, suggesting that gene expression changes may reflect functional alterations rather than cell number.ConclusionThese results highlight complex neurogenesis alterations in ASD and underscore the need for further research to identify biomarkers and potential therapeutic targets.